The ages and colours of cool helium-core white dwarf stars - Serenelli, Aldo Marcelo (2001)
The purpose of this work is to explore the evolution of helium-core white dwarf stars in a self-consistent way with the predictions of detailed non-grey model atmospheres and element diffusion. To this end, we consider helium-core white dwarf models with stellar masses of 0.406, 0.360, 0.327, 0.292, 0.242, 0.196 and 0.169 Msolar and follow their evolution from the end of mass-loss episodes, during their pre-white dwarf evolution, down to very low surface luminosities. We find that when the effective temperature decreases below 4000K, the emergent spectrum of these stars becomes bluer within time-scales of astrophysical interest. In particular, we analyse the evolution of our models in the colour-colour and in the colour-magnitude diagrams and find that helium-core white dwarfs with masses ranging from ~0.18 to 0.3Msolar can reach the turn-off in their colours and become blue again within cooling times much less than 15Gyr and then remain brighter than MV~16.5. In view of these results, many low-mass helium white dwarfs could have had enough time to evolve to the domain of collision-induced absorption from molecular hydrogen, showing blue colours.